Mechanism and treatment of secondary glaucoma after corneal transplantation: a review - Yumeng Lin; Yumeng Lin; Yumeng Lin; Qiaoyin Gou; Qiaoyin Gou; Qiaoyin Gou; Ping Yu; Ping Yu; Ping Yu; Zhengfang Wu; Zhengfang Wu; Zhengfang Wu; et al. (Frontiers in Ophthalmology, 2024)
Corneal transplantation is a common treatment for corneal diseases. Secondary glaucoma after corneal transplantation is the second leading cause of failure of keratoplasty. This article reviews the mechanism and treatment of secondary glaucoma after corneal transplantation.